(untitled) (Revista Ciência Agronômica, 2020)
There is interest in identifying the best maize and cowpea cultivars to be used in monocropped and intercropping systems for the production of dry grain. In order to meet this interest, two monocrops of cowpea (the traditional varieties, Corujinha and Sempre Verde) were evaluated with two monocrops of maize (the AG 1051 double hybrid and the AL Bandeirante variety) and four intercrops (combinations of the cowpea varieties and the maize cultivars). Under the intercropping systems, the maize and cowpea occupied alternating rows. A completely randomized block design with six replications was used. Grain growth and yield were higher in the AG 1051 hybrid than in the AL Bandeirante variety in both the monocropped and intercropping systems. For medium-sized maize grain, the growth and yield were higher in the monocrops than in the intercrops. It is unimportant which variety of cowpea, Corujinha or Sempre Verde, is used with each maize cultivar in the intercropping systems, as there was no interaction between the maize cultivars and the cowpea cultivars. In the monocropped systems, the grain yield of the Corujinha cultivar was greater than that of the Sempre Verde cultivar. Mean grain yield in the monocrops was greater than in the intercrops. Both cowpea cultivars showed better performance when intercropped with the AL Bandeirante maize cultivar than with the AG 1051 cultivar. The value of the land equivalent ratio was greater than 1.0 only for the combination of the AL Bandeirante variety of maize and the Sempre Verde variety of cowpea.